Aid diplomacy in Iraqi politics: humanitarian aid as a model - Muna Khazaal Khalifa Hussein; Sufyan Muhammad Ibrahim (Tikrit Journal For Political Science, 2023)
Discussing aid diplomacy in Iraqi politics, dealing with the issue of humanitarian aid as an important and vital topic in international relations. Humanitarian aid aims to address an emergency situation such as humanitarian disasters that afflict people and aims to provide the necessary humanitarian needs. government and various governments in order to save a human group in the event of a confirmed danger, its forms and principles that govern it, as well as dealing with the role of humanitarian aid in drawing Iraqi foreign policy and the most important models of this aid .